Athletes Greatly Benefit from Participation in Sports at the College and Secondary Level - James J. Heckman; Colleen P. Loughlin (Institute of Labor Economics (IZA), 2021)
The recent Supreme Court decision NCAA vs Alston (June 2021) has heightened interest in the benefits and costs of participation in sports for student athletes. Anecdotes about the exploitation of student athletes were cited in the opinion. This paper uses panel data for two different cohorts that follow students from high school through college and into their post-school pursuits to examine the generality of these anecdotes. On average, student athletes' benefit- often substantially so—in terms of graduation, post-collegiate employment, and earnings. Benefits in terms of social mobility for disadvantaged and minority students are substantial, contrary to the anecdotes in play in the media and in the courts.
Keywords: Z2; I32; I26; 330; sport economics; social mobility; returns to education